Pengembangan Lembar Kerja Peserta Didik Berbasis Interaktif pada Pembelajaran Matematika Kelas V di Madrasah Ibtidaiyah Ad’dawah - Ria Setia listi; Endang Mulia Kurnianti (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This study aims to develop an interactive-based Student Worksheet (LKPD) using a live worksheet. Mathematics subject, volume material on cubes and blocks for fifth grade elementary school. The type of research used is research and development (Research and Development) or called R&D. The research model used is ADDIE (Analysis, Design, Development, Implementation, Evaluations), the research consists of 5 stages. The subjects in the study were 15 students in the VC class. The instruments used are expert validation assessment questionnaires (materials, media, language), preliminary interview study sheets for teachers and students as well as teacher and student response questionnaires. Data collection techniques used in the form of teacher interviews, observation of learning activities and questionnaires. The results of the validation of the assessment of the LKPD were 82.35% material experts, 93% media experts and 80% linguists. The accumulation of the three experts obtained a percentage of 85%, which can be categorized as "Very Eligible". The teacher's assessment got 90%. Then the assessment of the student response questionnaires at the trial stage obtained 90.7% and the assessment at the field test stage obtained as much as 90.9%, so it can be categorized as "Very Good". So that it can be seen the effectiveness of the LKPD from the acquisition of an average score of 90.7. The conclusion in this study, that interactive-based LKPD using live worksheets is very suitable for use in learning mathematics, and this interactive LPKD gets a positive response from teachers and students.